2021
DOI: 10.2306/scienceasia1513-1874.2021.039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bio-organic fertilizer on soil fertility, microbial community composition, and potato growth

Abstract: The excessive and irrational use of chemical fertilizers poses a series of environmental problems. A growing number of research studies have focused on the application of beneficial microorganisms to reduce the use of chemical fertilizers. Here, potato field experiments were conducted to investigate whether partial replacement of chemical fertilizers with bio-organic fertilizers containing Bacillus velezensis BA-26 had an effect on plant growth, soil fertility, and soil microbial community composition. Three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The bacterial co-occurrence network was performed to reveal the interrelationships between species and the complexity of community structure and function [ 29 , 30 , 31 ]. Previous studies confirmed that alterations of community structure and bacterial network were closely related to soil properties, such as pH [ 32 ], soil matter organic [ 33 , 34 ] and available phosphorus [ 35 ], which have been considered major drivers of variation in biotopes. Although symbiotic network patterns were universally applied in forest ecosystems, the response of complex bacterial communities to the application of mixed organic and inorganic fertilizers in teak plantations is still unknown.…”
Section: Introductionmentioning
confidence: 87%
“…The bacterial co-occurrence network was performed to reveal the interrelationships between species and the complexity of community structure and function [ 29 , 30 , 31 ]. Previous studies confirmed that alterations of community structure and bacterial network were closely related to soil properties, such as pH [ 32 ], soil matter organic [ 33 , 34 ] and available phosphorus [ 35 ], which have been considered major drivers of variation in biotopes. Although symbiotic network patterns were universally applied in forest ecosystems, the response of complex bacterial communities to the application of mixed organic and inorganic fertilizers in teak plantations is still unknown.…”
Section: Introductionmentioning
confidence: 87%
“…Some complementary fertilization options other than the use of chemical fertilizers include the use of bio-surfactants [164], biomineralization [165] and biofertilizers [166][167][168], including microbial suspension and seaweed concentrate [25,169,170]. The use of plant growth-promoting microorganisms [171] is a very promising tool that could also have positive effects by inhibiting pathogens through the production of antibiotics or cell wall lytic enzymes, inducing plant defence mechanisms [172].…”
Section: Some Consideration For Organic Amendments Used As Fertilizermentioning
confidence: 99%
“…This could be due to the ability of microbes in solubilizing P and K. Bacillus cereus, for example, has been widely used in bio-organic fertilizer and plant booster to solubilize the unavailable form of P from soil (PO [3][4] ) to available P (HPO 2-4 and H 2 PO -4 ) and to solubilize exchangeable K which resulted in soil bearing K [39]. In recent study, bio-organic fertilizer Bacillus velezensis has been reported to improve physico-chemical properties of soil such as organic matter and available P, K, and N and support potato growth with good tuber quality [40].…”
Section: Nutrient Availabilitymentioning
confidence: 99%